Successful transition from insulin to sulfonylurea, on second attempt, in a 24-year-old female with neonatal diabetes secondary to KCNJ11 gene mutation. Issue 4 (9th April 2021) - Hajji, Sulaiman; Aljenaee, Khaled; Garrahy, Aoife; Byrne, Maria
Abstract : Neonatal diabetes (NDM) is defined as diabetes that occurs in the first 6 months of life, the majority of cases are due to sporadic mutations. ATP-sensitive potassium channels located in the beta cells of the pancreas play a major role in insulin secretion and blood glucose homeostasis. Mutations that alter the function of these channels may lead to NDM. We report a case of a 26-year-old Irish woman who was diagnosed with NDM at the age of 4 weeks and treated as type 1 diabetes mellitus, with multiple daily injections of insulin with suboptimal glycaemic control and frequent episodes of hypoglycaemic. She underwent genetic testing for NDM and was diagnosed with a KCNJ11 gene mutation. She was transitioned to high dose glibenclamide at the age of 16 years, but the trial failed due to poor glycaemic control and patient preference, and she was restarted on insulin. At 24 years of age, she was successfully transitioned from insulin (total daily dose 50 units) to high dose sulfonylurea (SU) (glibenclamide 15 mg twice daily). This resulted in optimal control of blood glucose (HbA1C fell from 63 to 44 mmol/mol), lower rates of hypoglycaemic and better quality of life. This case demonstrates that a second trial of SU in later life may be successful.